Mid-upper arm circumference as a screening tool for identifying underweight adolescents - Musa, Imad R.; Omar, Saeed M.; AlEed, Ashwaq; Al-Nafeesah, Abdullah; Adam, Ishag (Frontiers in Nutrition, 2023)
Background: Mid-upper arm circumference (MUAC) is a potentially credible alternative method for body mass index (BMI) to assess nutritional status. We aimed to access the correlation between MUAC and BMI-Z-score and to identify a reliable MUAC cut-off point to detect underweight (BMI-Z-score of < -2standard deviation) among Sudanese adolescents.Methods: A cross-sectional study was conducted in eastern Sudan. After obtaining adolescents' age and sex, their weight, height and MUAC were measured using the standard procedures. The MUAC (cm) cut-off corresponding underweight was calculated using receiver operating characteristic (ROC) curve analysis.Results: Three hundreds and ninety adolescents were enrolled in the study and 205 (52.6%) of them were females. The median (interquartile range, IQR) of the age was 15.1 (14.0 -16.3) years.The medians (IQR) of MUAC and BMI-Z-score was 22.0 (20.0 -24.0), cm and -0.62 (-1.5 -0.3), respectively. MUAC was positively correlated with BMI Z-score in all participants (r = 0.534, p < 0.001), in females (r = 0.715, p < 0.001) and in males (r = 0.404, p < 0.001). Of the 390 enrolled adolescents, 61(15.6%) were underweight. The MUAC cut-off for underweight was ≤ 21.2cm in all participants (Youden's Index, YI= 0.50; sensitivity = 82.0%; specificity = 68.0%, AUROCC = 0.78, in females (YI = 0.66, sensitivity = 86.0%, specificity = 80.0%, AUROCC = 0.87) and in males (YI = 0.32, sensitivity = 80.0%, specificity = 52.0%, AUROCC = 0.69.MUAC has good accuracy results and can be adopted for community-based to screen underweight.